2021
DOI: 10.1155/2021/5516100
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 and Immune Infiltration of m6A RNA Methylation Regulators and Its miRNA Regulators in Hepatocellular Carcinoma

Abstract: Background. The aim of this study was to systematically evaluate the relationship between the expression of m6A RNA methylation regulators and prognosis in HCC. Methods. We compared the expression of m6A methylation modulators and PD-L1 between HCC and normal in TCGA database. HCC samples were divided into two subtypes by consensus clustering of data from m6A RNA methylation regulators. The differences in PD-L1, immune infiltration, and prognosis between the two subtypes were further compared. The LASSO regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Previous studies have revealed that m6A methylation regulators are associated with RNA translation disorders in cancer occurrence and development [ 24 , 25 ]. However, more and more evidence shows that this process not only occurs in tumors but also occurs in various diseases [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that m6A methylation regulators are associated with RNA translation disorders in cancer occurrence and development [ 24 , 25 ]. However, more and more evidence shows that this process not only occurs in tumors but also occurs in various diseases [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…DF2 has the same effect of immune promotion in intrahepatic cholangiocarcinoma (ICC). DF2 directly recognized the m6A 3′UTR region of PD-L1 mRNA and promotes its degradation in an m6A-dependent manner [ 139 ]. DF2 expression enhanced NK cells proliferation, homeostasis, IL-15-mediated survival, and antitumor ability.…”
Section: Yth Domain-containing Proteins Function As M6a Readers In Ca...mentioning
confidence: 99%
“…In pancreatic cancer cells, miR-142-5p inhibits PD-L1 expression and suppressed in vivo tumor growth, suggesting its reinforced expression to potentiate ICPIs treatment [ 77 ]. Interestingly, miR-142-5p influences the tumor microenvironment, PD-L1 expression and HCC prognosis by targeting m 6 A RNA methylation regulators [ 78 ], warranting its validation in advanced HCC undergoing immunotherapy. Beside immunoediting functions, miR-142 also plays a relevant oncogenic role.…”
Section: Micrornas Directly Targeting Pd-l1mentioning
confidence: 99%